Geomorphic indexes of tectonic activity through the analysis of the drainage systems in the Sangaw area, Kurdistan Region –Geomorphic indexes of tectonic activity through the analysis of the drainage systems in the Sangaw area, Kurdistan Region – NE-Iraq - Bety, Azhar Kh. S. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Different geomorphic indicators like drainage basin asymmetry (AF), transverse topographic symmetry factor (T), mountain front sinuosity (Smf) and ratio of valley floor width to valley height (Vf) was obtained from the Sangaw basin to study the tectonic activities in Sangaw district area, which it located within the administrative boundaries of the Sulaimani City, Kurdistan Region – NE-Iraq. Geographic Information System (GIS) was used in the calculation of the geomorphic indicators and in order to study, analyze and classify tectonic activity. The results of geomorphic indicators with respect to the visual interpretation of satellite image, DEM and field observation shows that the area is tectonically active, and the activity is is tectonically active, and the activity is ranging between moderate to high activities.
Keywords: drainage basin; geomorphic index; tectonic activity GIS